PENGARUH FINANCIAL BEHAVIOR DAN LITERASI KEUANGAN TERHADAP SAVING BEHAVIOR - wildayati, wildayati (REKAMAN (Jurnal Riset Ekonomi Bidang Akuntansi dan Manajemen), 2018)
This study aimed to examine the effect of Financial Behavior and Financial Literacy on Saving Behavior case study on the student of Akademi Akuntansi Permata Harapan. The population of this study is all students of Akademi Akuntansi Permata Harapan. The techniques used in the sampling is puposive sampling that is with criterion of students who already get subject of Introduction of Accounting. Data analysis used is multiple linear regression analysis. These results of this study indicate that the Financial Behavior and Financial Literacy either partially or simultaneously affect Saving Behavior. This is evidenced by the t-test of the sig. value Financial behavior that is 0.000 < Î± = 0.05 and Financial Literacy variable that is 0.000 < Î± = 0.05. While the F test result obtained sig. value of Â 0.000 < Î± = 0.05.